2013
DOI: 10.1016/j.biopsycho.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception use alters stress responses and emotional memory

Abstract: Emotionally arousing material is typically better remembered than neutral material. Since norepinephrine and cortisol interact to modulate emotional memory, sex-related influences on stress responses may be related to sex differences in emotional memory. Two groups of healthy women – one naturally cycling (NC women, N = 42) and one using hormonal contraceptives (HC women, N = 36) – viewed emotionally arousing and neutral images. Immediately after, they were assigned to Cold Pressor Stress (CPS) or a control pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
88
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 30 publications
9
88
1
Order By: Relevance
“…There might be differences in the association of cortisol and memory in women in different stages of the cycle. We additionally conducted separate analyses for women taking hormonal contraceptives and women not using hormonal contraceptives given the reported differences in responses to stress effects on memory (e.g., Nielsen, Segal, Worden, Yim, & Cahill, 2013). However, we did not find any significant differences between correlation coefficients between these groups.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There might be differences in the association of cortisol and memory in women in different stages of the cycle. We additionally conducted separate analyses for women taking hormonal contraceptives and women not using hormonal contraceptives given the reported differences in responses to stress effects on memory (e.g., Nielsen, Segal, Worden, Yim, & Cahill, 2013). However, we did not find any significant differences between correlation coefficients between these groups.…”
Section: Discussionmentioning
confidence: 89%
“…Including B2 as covariate did not alter the result pattern (association with long-delay recall performance: r = −0.14, R 2 = 1.96%; p (uncorrected) = .000001; association with short-delay recall performance: r = −0.11, R 2 = 1.21%; p (uncorrected) = .00007). Given the differences in responses to stress effects on memory in women using hormonal contraceptives and women not using hormonal contraceptives (e.g., Nielsen, Segal, Worden, Yim, & Cahill, 2013), we additionally conducted separate analyses in women taking hormonal contraceptives and women not using hormonal contraceptives. Descriptively, associations were stronger for women not using hormonal contraceptives (r = −0.19, R 2 = 3.61%; p (uncorrected) = .0003) than for women taking hormonal contraceptives (r = −0.10, R 2 = 1.0%; p (uncorrected) = .04); for association between decrease in cortisol levels during recall on Day 2 (B3-B2) and long-delay recall performance.…”
Section: Change In Cortisolmentioning
confidence: 99%
“…Hormonal contraceptives/hormonal birth control (hereafter abbreviated HBC) is known to affect responses to laboratory stress (Kirschbaum et al, 1999; Nielsen et al, 2013). Women taking HBC have distinct HPA axis signatures compared to those not taking HBC, including lower cortisol awakening responses (Pruessner, Hellhammer, & Kirschbaum, 1999); a lower salivary cortisol response to psychosocial stress (Kirschbaum, Pirke, & Hellhammer, 1995); a blunted cortisol response to physical exercise (Bonen, Haynes, & Graham, 1991; Kirschbaum, Pirke, & Hellhammer, 1996); greater glucocorticoid sensitivity to pro-inflammatory cytokines after acute stress (Rohleder, Wolf, Piel, & Kirschbaum 2003); and altered circadian cortisol (Bouma et al, 2009; Pruessner et al, 1997; Reinberg et al, 1996, but refer to Wust et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, since HC profoundly alters HPG activity and HPA reactivity (Bentz et al, 2013;Kirschbaum, Kudielka, Gaab, Schommer, & Hellhammer, 1999;Nielsen, Ahmed, & Cahill, 2013;Nielsen, Segal, Worden, Yim, & Cahill, 2013) and the HPG and HPA axes have a bi-directional relationship (Turner, Keating, & Tilbrook, 2012), it is likely that under conditions of arousal and/or stress, use of hormonal contraceptives alters learning and memory in these women.…”
mentioning
confidence: 98%
“…For example, studies involving exogenous cortisol administration found that verbal retrieval (Kuhlmann & Wolf, 2005) and fear learning (Merz et al, 2012) were modified in hormonal contraceptive users compared to naturally cycling (NC) women and men. Other work has utilised classical conditioning paradigms (Beck et al, 2008;Holloway, Beck, & Servatius, 2011;Merz, Stark, Vaitl, Tabbert, & Wolf, 2013; and longterm memory paradigms with an emotional story (Nielsen, Ertman, Lakhani, & Cahill, 2011;Nielsen, Ahmed, et al, 2013) and emotional images (Nielsen, Segal, et al, 2013) to demonstrate that women on HC exhibit altered learning and memory patterns under arousal and stress.…”
mentioning
confidence: 99%